Metabolic syndrome in pregnancy and associated factors in pregnant women - Ajorloue, Zeinab; Moghaddam-Banaem , Lida; shokri, masoumeh; Taleby Anvare, Afsaneh; Parizade, Ali (Researcher Bulletin of Medical Sciences, 2024)
Background: Due to changes in lifestyle and the rising incidence of metabolic syndrome in different societies, aim of this study was to evaluate factors associated with metabolic syndrome in pregnancy. Materials and Methods: This cross-sectional study was performed in the years 2015 - 2016 on 500 pregnant women in their first trimester of pregnancy who attended for routine tests Niloo laboratory in Tehran. A demographic /reproductive questionnaire was completed for all pregnant women by the researcher at time of entry into the study. Inclusion criteria were gestational age less than 14 weeks, no history of systemic diseases including diabetes, and singleton pregnancy. The mothers weight, height and blood pressure (BP)were measured and their BMI (Body mass Index) was calculated . A fasting blood sample was obtained for measuring fasting blood sugar (FBS) triglyceride (TG) and High-Density Lipoprotein (HDL) levels. If the mother had 3 or more of the following criteria, they were considered as having gestational metabolic syndrome (GMS) .1-Pre-pregnancy BMI ≥ Kg/m2 ,2- FBS≥100 mg/dl, 3-TG≥150mg/dl, 4-HDL<50mg/dl, 5-BP≥130/85mm/Hg. The data analysis was performed using the software SPSS21, K 2, t-test and P <0.05 was considered as significant level. Results: The occurrence of gestational metabolic syndrome was observed in 21 (4% of mothers) happened. In K2 analysis, folic acid intake had a significant protection effect on GMS (P-value:0.014), in T-test pre-pregnancy BMI (P-value<0.001). Conclusion: In this study, pre-pregnancy BMI and increased number of pregnancies were associated with an increased incidence of gestational metabolic syndrome. But folic acid intake was a protective factor in reducing the risk of metabolic syndrome. These results need to be further evaluated in future studies.